Pulsating flow of Casson fluid in a porous channel with thermal radiation, chemical reaction and applied magnetic field - Srinivas, Suripeddi; Kumar, Challa Kalyan Kalyan; Reddy, Anala Subramanyam Subramanyam (Nonlinear Analysis: Modelling and Control, 2018)
In the present analysis, the influence of thermal radiation, chemical reaction and thermal-diffusion on hydromagnetic pulsating flow of Casson fluid in a porous channel is investigated. The fluid is injected from the lower wall and sucked out from the upper wall with the same velocity. The governing flow equations are solved analytically by employing the perturbation technique. The influence of various emerging parameters on flow variables has been discussed. The obtained results show that the temperature distribution increases when there is an increase in heat source, whereas there is a decrease in temperature with an increase in radiation parameter. The concentration distribution decreases with an increase in chemical reaction parameter, while it increases for a given increase in Soret number. Further, the results reveal that, for both the Newtonian and non-Newtonian cases, Nusselt number distribution decreases at the upper wall with increasing Hartmann number and radiation parameter. The mass transfer rate decreases at the upper wall with increasing chemical reaction parameter and Soret number.